2014
DOI: 10.3109/09687637.2014.956051
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and attendance patterns of a fixed-site NSP and nearby SVM: The benefits of 24-hour access to sterile injecting equipment

Abstract: Aims: This article describes the characteristics and attendance patterns of clients of a co-located fixed-site needle and syringe program (NSP) and syringe vending machine (SVM) to assess the utilisation and benefits of providing access to multiple distribution services. Methods: Data were collected through cross-sectional surveys with a convenience sample of NSP (n ¼ 98) and SVM (n ¼ 91) recruited attendees in Sydney, Australia. Surveys collected demographic data, selfreported injecting patterns, self-reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…In addition to SSPs, other public health strategies communities may consider implementing to ensure access to sterile injection equipment and minimize COVID-19 risks. For example, implementing public health vending machines, sometimes referred to as syringe vending machines, may hold promise for increasing access to harm reduction resources for populations underserved by the more traditional SSP model [ 22 , 23 ]. Mail-based supply distribution may also be of public health utility, particularly for meeting the needs of PWID residing in isolated areas with limited SSP access [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to SSPs, other public health strategies communities may consider implementing to ensure access to sterile injection equipment and minimize COVID-19 risks. For example, implementing public health vending machines, sometimes referred to as syringe vending machines, may hold promise for increasing access to harm reduction resources for populations underserved by the more traditional SSP model [ 22 , 23 ]. Mail-based supply distribution may also be of public health utility, particularly for meeting the needs of PWID residing in isolated areas with limited SSP access [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…To consider for a moment the relevance of this approach, however, we sometimes assume that NSPs deliver convenience, and that where there are gaps, vending machines could fill them. This is certainly part of the picture (Cama et al, 2014), but as this theory proposes (and as our interviews, discussed later, also suggest) convenience is more complicated than this. In addition, convenience, especially if narrowly defined, is not always the main priority for consumers.…”
Section: Approachmentioning
confidence: 99%
“…This could be seen as fundamentally a matter of coverage, which is undoubtedly a key issue for prevention (Cama et al, 2014). But convenience is more than this suggests.…”
Section: Conveniencementioning
confidence: 99%
“…Several studies have shown that some people who use ADMs differ from those who access face-to-face NSPs or pharmacies for injecting equipment, reporting that primary ADM users were younger, had shorter durations of injecting, injected less frequently, were less likely to report risky injecting practices or to have received opioid agonist treatment (OAT) [ 5 , 7 , 17 , 18 ]. However, two recent Australian studies suggested that when ADMs were located adjacent to face-to-face NSPs and near pharmacies, the ADM was primarily used by clients of face-to-face services who used the ADM outside business hours [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In regard to HCV prevention and testing, some studies report that people who use ADMs report less syringe sharing [ 16 ] and do not differ from those who primarily use face-to-face NSPs in terms of HCV risk practices [ 8 , 20 , 21 ]. However, uptake of HCV testing and particularly treatment among people who use ADMs remains unclear, including potential gender differences.…”
Section: Introductionmentioning
confidence: 99%